2017
DOI: 10.1016/j.jsps.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Study on apoptosis effect of human breast cancer cell MCF-7 induced by lycorine hydrochloride via death receptor pathway

Abstract: As research was conducted on the early apoptosis of human breast cancer cell MCF-7 caused by lycorine hydrochloride and the expression of the related apoptosis proteins. The early-period apoptosis rate of human breast cancer cell MCF-7 was tested with the AnnexinV/PI double staining and flow cytometry. The Western Blotting method was also used to detect the protein expression conditions of Fas, FasL, Caspase-8 and Bid. The results showed that the higher the dose, the higher the rate of apoptosis and that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…Lycorine induces G1 phase cell cycle arrest in multiple myeloma and chronic myelocytic leukemia cell lines with downregulation of cyclin D and CDK4 [80,87,88]. Whereas, in ovarian cancer cell line HeyB1 and acute promyelocytic leukemia cell line HL-60 this compound induces cell cycle arrest at G2/M phase [65,85]. In response to growth factors, CDK4 and CDK6 combined with one of several D-type cyclins in early G1 phase.…”
Section: Cell Cycle Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lycorine induces G1 phase cell cycle arrest in multiple myeloma and chronic myelocytic leukemia cell lines with downregulation of cyclin D and CDK4 [80,87,88]. Whereas, in ovarian cancer cell line HeyB1 and acute promyelocytic leukemia cell line HL-60 this compound induces cell cycle arrest at G2/M phase [65,85]. In response to growth factors, CDK4 and CDK6 combined with one of several D-type cyclins in early G1 phase.…”
Section: Cell Cycle Inhibitionmentioning
confidence: 99%
“…For the induction of extrinsic or death receptor pathway of apoptosis, lycorine was reported to activate death receptor ligands of the tumor necrosis factor (TNF) family TNF-α leading to caspase 8 activation [68,80,84]. It was also found that lycorine decreases the caspase-8 substrate Bid and significantly increases the expression level of truncated form of Bid protein (tBid) with a concomitant release of cytochrome C and activation of caspase-9 and caspase-3, indicating the Bid mediated crosstalk between mitochondria and death receptor apoptotic pathways upon lycorine treatment [84,85]. Lycorine also increases the portion of apoptotic cells in vivo xenografted tumor models.…”
Section: Apoptosis Inductionmentioning
confidence: 99%
“…The dichloromethane extracts, three alkaloids (lycorine, vittatine and montanine) exhibited potential antiproliferation activity in MCF7 breast cancer cells (Silva et al, 2008). Furthermore, it could induce the apoptosis of MCF7 (Ji et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…28 Fas and FasL, which induced cell apoptosis, were activated in a report related to the effect of lycorine hydrochloride on MCF-7 cells. 29 In differentiated cells, DNMT1 activated p53 to regulate programmed cell death. 30 It has been confirmed that p53, as a dominant regulator of the apoptotic framework, can regulate extrinsic and intrinsic apoptosis pathway signaling cascades.…”
Section: Discussionmentioning
confidence: 99%